The Ascension Island Boundary Layer in the Remote Southeast Atlantic is Often Smoky. Issue 9 (11th May 2018) - Zuidema, Paquita; Sedlacek, Arthur J.; Flynn, Connor; Springston, Stephen; Delgadillo, Rodrigo; Zhang, Jianhao; Aiken, Allison C.; Koontz, Annette; Muradyan, Paytsar
Abstract: Observations from June to October 2016, from a surface‐based ARM Mobile Facility deployment on Ascension Island (8°S, 14.5°W) indicate that refractory black carbon (rBC) is almost always present within the boundary layer. The rBC mass concentrations, light absorption coefficients, and cloud condensation nuclei concentrations vary in concert and synoptically, peaking in August. Light absorption coefficients at three visible wavelengths as a function of rBC mass are approximately double that calculated from black carbon in lab studies. A spectrally‐flat absorption angstrom exponent suggests most of the light absorption is from lens‐coated black carbon. The single‐scattering‐albedo increases systematically from August to October in both 2016 and 2017, with monthly means of 0.78 ± 0.02 (August), 0.81 ± 0.03 (September), and 0.83 ± 0.03 (October) at the green wavelength. Boundary layer aerosol loadings are only loosely correlated with total aerosol optical depth, with smoke more likely to be present in the boundary layer earlier in the biomass burning season, evolving to smoke predominantly present above the cloud layers in September–October, typically resting upon the cloud top inversion. The time period with the campaign‐maximum near‐surface light absorption and column aerosol optical depth, on 13–16 August 2016, is investigated further. Backtrajectories that indicate more direct boundary layer transport westward from the African continent is central to explaining the elevated surface aerosol loadings. Plain Language Summary: First findings from the remote Ascension Island midway between Africa and South America in the Atlantic Ocean indicate that smoke is present much more often near the surface than has been previously thought. The new measurements from a 17‐month‐long campaign suggest that August is the smokiest month near the surface. The smoke includes other aerosols besides black carbon, and is most absorptive of sunlight in June and least in October. The smoke is more present near the surface earlier in the biomass burning season, or June, while later on toward September and October, more of the smoke resides above the cloud layer. This has implications for which aerosol‐cloud microphysical and radiative interactions are dominant when. The campaign‐maximum aerosol loading event is investigated further and attributed to an unusual direct westward flow from the continental African fire sources at low altitudes. Key Points: Refractory black carbon is often present in the remote marine boundary layer of the southeast most significantly from June to August A spectrally flat absorption angstrom exponent suggests that most light absorption is from lens‐coated black carbon The single‐scattering albedo increases from an August mean of 0.78 to 0.81 in September and 0.83 in October